Radość, duma, niepokój? kilka lingwistyczno-kulturologicznych uwag o emocjach filmowców utrwalonych w "Zagrajcie mi to pięknie. <Pan Tadeusz> według Andrzeja Wajdy" Marka Millera = Joy, pride, ankiety? a few linguistic-culturological remarks on the filmmakers` emotions preserved in "Zagrajcie mi to pięknie. <Pan Tadeusz> according to Andrzej Wajda" by Mark Miller - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The essay is focused on the experiences of the creators of the screen adaptation of the Polish national epic "Pan Tadeusz". The comments recorded in an extended interview prepared by Mark Miller and his co-workers provide a valuable source of knowledge not only for filmmakers but also for everybody to whom native cultural heritage is important.
Keywords: film; twórcy; emocje; werbalizacja; język; wywiad; poemat epicki; filmmakers; emotions; verbalization; language; interview; epic poem